THE LEGAL STATUS OF THE DEFENDER IN CRIMINAL PROCEEDINGS, THE COSTS INCURRED IN THEIR INVOLVEMENT AND THE ASPECTS THAT SHOULD BE TAKEN INTO ACCOUNT WHEN COVERING THE COSTS - Bozorov Maqsudali Maxmudovich (Modern American Journals, 2026)
Issues related to the participation of the defense attorney in criminal proceedings, as well as existing costs of involving the defense counsel by the preliminary investigative authorities and the court, and the problems of their subsequent transfer to the prisoner.The article stipulates issues related to the participation of the defense attorney appointed in criminal proceedings, as well as ensuring the participation of the investigator, investigator, prosecutor or lawyer who provides legal aid at the expense of the state in the manner prescribed by the Law of the Republic of Uzbekistan "On the provision of legal aid at the expense of the state" in the manner prescribed by the Law of the Republic of Uzbekistan "On the provision of legal aid at the expense of the state", the imposition of state funds paid to the lawyer on the prisoner, The existing problems in this process have been analyzed and proposals for improving the legislative acts have been noted.
Keywords: Procedural costs, participation of the defender, Provision of legal aid at the expense of the state, transfer of costs to the state account, attribution of costs to the defendant.